2023
DOI: 10.1038/s41398-023-02370-0
|View full text |Cite
|
Sign up to set email alerts
|

Cross-tissue correlations of genome-wide DNA methylation in Japanese live human brain and blood, saliva, and buccal epithelial tissues

Abstract: Neuroepigenetics considers genetic sequences and the interplay with environmental influences to elucidate vulnerability risk for various neurological and psychiatric disorders. However, evaluating DNA methylation of brain tissue is challenging owing to the issue of tissue specificity. Consequently, peripheral surrogate tissues were used, resulting in limited progress compared with other epigenetic studies, such as cancer research. Therefore, we developed databases to establish correlations between the brain an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…Furthermore, our novel cell type-specific short RNA-seq dataset from live human brain Tssues is prone to be biased by the pathology effect. We showed that the extracted profiles are closer to those of healthy postmortem brains than to meningioma samples (Supplementary Figure 3), similar to mulTple previous studies on live human brain Tssue, which suffered from the same limitaTon 4850 . However, we cannot fully rule out the possibility that the extracted neuronal and microglial profiles are affected by the tumor.…”
Section: Introductionsupporting
confidence: 86%
“…Furthermore, our novel cell type-specific short RNA-seq dataset from live human brain Tssues is prone to be biased by the pathology effect. We showed that the extracted profiles are closer to those of healthy postmortem brains than to meningioma samples (Supplementary Figure 3), similar to mulTple previous studies on live human brain Tssue, which suffered from the same limitaTon 4850 . However, we cannot fully rule out the possibility that the extracted neuronal and microglial profiles are affected by the tumor.…”
Section: Introductionsupporting
confidence: 86%
“…33 ATE1 is crucial for the normal development of the mouse brain, and the lack of this gene results in misleading neurite outgrowth and localization of doublecortin in growth cones. 34 The results of our AMAZE-CpG database show that the brain-blood of this CpG site is positively correlated (rho adj = 0.50, P adj = 0.03) 24 . These ndings suggest that methylation of ATE1 may have delayed OFrC development due to the consequences of the failure of attachment formation resulting from CM.…”
Section: Discussionmentioning
confidence: 98%
“…Saliva cell composition comprises ∼80% immune cells and ∼20% epithelial buccal cells (Zheng et al, 2018). This cell composition similarity likely results in strong correlations ( r ∼0.97) between saliva and blood DNAm patterns (Nishitani et al, 2023). This is higher than the blood-saliva correlations typically observed when directly measuring inflammatory markers (such as salivary CRP) (Szabo & Slavish, 2021).…”
Section: Discussionmentioning
confidence: 99%